ON THE ISSUE OF REASONS AND MEANS OF FORMULATION OF CORPUS DELICTI WITH ALTERNATIVE SIGNS OF OBJECTIVE PART - R. R. Musina (Russian Journal of Economics and Law)
The article reveals the notion of corpus delicti with alternative signs of objective part, gives recommendations on formulating the corpus delicti with alternative signs of objective part when creating new normative-legal acts, and describes the substantial alternative signs of objective part.